А) 13-5х=8-2х
б) 5х+(3х-7)=9
в) (7х+1)-(6х+3)=5
г) 5(3х+2)-4х=11х+10

karahenov98Алекс karahenov98Алекс    3   19.10.2019 18:25    1

Ответы
Taniusha02 Taniusha02  10.10.2020 08:01

13 - 5х = 8 - 2х

-5х + 2х = 8 + 13

-3х = 21

х = 21/-3

х = -7

5х + (3х - 7) = 9

5х + 3х - 7 = 9

8х = 9 + 7

8х = 16

х = 16/8

х = 2

(7х + 1) - (6х + 3) = 5

7х + 1 - 6х - 3 = 5

х = 5 - 1 + 3

х = 7

5(3х + 2) - 4х = 11х + 10

15х + 10 - 4х = 11х + 10

11х - 11х = 10 - 10

0х = 0, => не имеет решения

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра